The Use of Lego Kits as Manipulatives, The Academic Performance, and the Spatial Ability of Grade 9 - Science Students - Subang, Lavi Cornel (Archīum Ateneo, 2020)
Chemistry tries to understand the structures and the processes involved in different substances. Physical models or manipulatives are often used to represent these structures, and other Chemistry concepts, to foster better understanding of the lesson. The commercial ball and stick model manipulative kits are the go-to manipulative for Chemistry teachers especially for the discussion of Lewis structures and molecular geometry. LEGO®, on the other hand, is a famous toy that releases sets that can be used to teach STEM topics, but not including Chemistry. This research determined the effects of LEGO® manipulative kits on the academic performance and spatial ability of Grade 9- Science students and tried to compare the effects to that of the what is traditionally used in the classroom (commercial ball and stick model kits). The students who used the LEGO kits enjoyed the activity to an extent that not all of the students were able to finish the activity. On the other hand, the students in the traditional manipulative group had a hard time using the ball and stick model kits and needed more assistance from the teacher. Also. results of the study showed that there is a statistically significant difference on the initial and final academic performance and spatial analysis score percentages of the traditional manipulative group and the LEGO® manipulative group, but there is no statistically significant difference in the score percentages between the two groups. Based from the results of this study, it was concluded that both manipulatives can help the students visualize chemistry concepts, and the LEGO kits can be further improved by incorporating a customized brick as the central atom for the kit.